The Role of Extended Family Structure in Moderating the Impact of War Trauma in the Middle East: A Cultural Analysis - M. Agung Rahmadi; Helsa Nasution; Luthfiah Mawar; Nurzahara Sihombing (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
This meta-analysis systematically and comprehensively examines the structural and functional roles of the extended family in moderating the psychological impact of war trauma in the Middle East by compiling data from 47 independent studies involving 12,483 participants published between 2000 and 2023. An analytical approach using a random-effects model revealed that the presence and involvement of the extended family demonstrated a statistically significant moderating effect on the reduction of PTSD symptoms, anxiety, and depression, with an association strength of r = .42 (p < .001). Further meta-regression results indicated that support from the extended family contributed to a 37.8% reduction in PTSD symptoms (β = -.378, SE = .042, p < .001), a 29.4% decrease in anxiety levels (β = -.294, SE = .038, p < .001), and a 31.2% reduction in depressive symptoms (β = -.312, SE = .040, p < .001). Analysis of moderator variables showed that the protective effect of the extended family structure was more pronounced among children (r = .48) compared to the adult population (r = .38) and more salient among females (r = .45) than males (r = .39), indicating demographic sensitivity to the type of collective support received. Moreover, the high heterogeneity across studies (I² = 76.3%) indicated significant contextual and methodological diversity, though it did not obscure the core findings. These results contradict the theoretical emphasis advanced by Nakeyar and Frewen (2016) and Atallah (2017), who prioritized the role of the nuclear family in post-war healing contexts. In contrast, this study found that the extended family configuration has provided a more comprehensive and multidimensional form of psychological protection rooted in the distinct collectivistic values of Middle Eastern societies. Ultimately, these findings expand the conceptual horizon for understanding resilience mechanisms to trauma within non-Western cultural landscapes and open new possibilities for developing extended family-based interventions in the context of post-conflict psychosocial reconstruction.